Utility of urethral ratio in voiding cystourethrogram to identify milder variants of posterior urethral valves - Ainippully, Arun M.; P. V., Anoop; V., Arun; S., Prathap (International Surgery Journal, 2018)
Background: Majority of patients with posterior urethral valves are diagnosed antenatally. Few patients present later in childhood with milder variants of the disease where the radiological findings are not very apparent. In this study, we aim to evaluate the role of urethral ratio beyond which here is higher probability of finding a mild variant of urethral valve thereby identifying patients who need to undergo a cystoscopic evaluation. Methods: This study was conducted in the Department of Paediatric Surgery between 2016 and 2017. 48 male patients who presented with either urinary tract infection or other lower urinary tract symptoms were included in the study. The candidates were examined and evaluated with an ultrasound followed by a voiding cystourethrogram (VCUG). The Urethral ratio was calculated. All patients then underwent a cystoscopy to rule out the presence of valve. We analyzed the data in Stata IC 15 statistical software and R statistical computing environment. Results: Of the 48 children recruited to the study, the median age of those with posterior urethral valve on cystoscopy was 8(IQ 3-18) and those without valves was 9(IQ 6.5-21) months. There was a statistically significant difference in the quality of urinary stream, straining on micturition, presence or absence of palpable bladder between the two groups (p value <0.05). The mean urethral ratio in the first group with PUV was 2.25(CI 2.02 to 2.48) and that in the second group with no urethral valve was 1.48(CI 1.32 to 1.65). with cut-off point of Urethral ratio at 2 the specificity and positive predictive value for the presence of PUV reached 100%. Conclusions: The present study indicates the calculation of urethral ratio on VCUG is an objective method for assessment of milder variants of PUV. In the present study, a Urethral ratio greater than 2 had a positive predictive value of 100% and would mandate a cystoscopic evaluation.